Current Trends in the Therapeutic Strategies for Diabetes Management - Sivakumar, Ponnurengam M.; Prabhawathi, Veluchamy; Zarrabi, Ali; Akthar, Sohail; Prabhakar, Pranav Kumar (Current Medicinal Chemistry, 2021)
Diabetes mellitus is one of the fastest-growing non-communicable diseases. Diabetes mellitus is caused due by the destruction of pancreatic β-cell or due to insulin resistance and characterized by hyperglycemia. Diabetes imposes a very serious economic crisis as the diabetic drug market is growing very rapidly. Even after very path-breaking scientific discoveries, the availability of better healthcare infrastructure, and a rise in literacy rates, the diabetes burden is continuously spreading in various sections all over the world but more especially in low- and middle-income countries. The recent developments in scientific discoveries have given several new generations of antidiabetic medicines such as sulphonylurea, biguanides, thiazolidinedione, α-glucosidase inhibitors. All these drugs have proved a significant reduction in blood glucose level. There are some new classes of hypoglycaemic drugs that have also been developed and reported, such as GLP-1 analogous, DPP-IV inhibitors, amylin inhibitors, and peroxisome proliferator- activated receptors. There are some active molecules and bioactive substances that have been purified from herbs and plants, which add value to the war against diabetes. These phytoconstituents have overturned drug development and lead identification for drugs against diabetes. The review also focuses on some critical areas of diabetes with more focus on statin-based diabetes management approach and stem cell therapy based next generation antidiabetic therapy.
Keywords: sulphonylurea